PERWUJUDAN SPIRITUALITAS BELAS KASIH MENURUT PAUS FRANSISKUS DALAM PELAYANAN PASTORAL KORBAN PELECEHAN SEKSUAL - Oktaviana, Oktaviana (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
Lately there have been cases of sexual harassment in Indonesia. The stigma that has developed in society that demeans victims of harassment has succeeded in silencing the voice of truth that was about to be echoed. This causes lasting trauma. Pope Francis offers a cure for the hurt that is happening in the world today. The medicine is the Spirituality of Compassion which is manifested in pastoral care for victims of sexual abuse. The spirituality of compassion, according to Pope Francis, is described through the firm faith of a mother who cares for injured children. The mother does not wait for the injured to knock on her door but goes out to find, collect, hug, nurse and make them feel loved. This spirituality enables a person to read the hearts of those he meets and respond to their deepest needs. The spirituality of compassion is on the side of those who are branded guilty, evil and despised. The author personifies himself as a good Samaritan who is present to approach a wounded person. In the process of digging up wounds, the author uses a compassionate approach as Jesus did to the Samaritan woman at Jacob's well. Jesus looked at him with compassion. There is hope that through this process at least the victim can rise and move forward. There is hope that the impact of the wound will no longer make the victim feel hopeless.